Acordo Coletivo com propósito específico e o projeto de lei 4193/2012: as convergências em torno de uma pretensa desregulamentação trabalhista via negociação coletiva. - Silva, Ana Flavia Dantas Figueirêdo (2014)
The dissertation aims to examine the draft bill called the Collective Bargaining Agreement for specific purposes / Special Collective Agreement-ACE, created by the ABC Metalworkers' Union and delivered in early 2011 the Federal Executive Power and the bill authored 4193 2012 deputy Irajá Abreu. The bill proposes legislative changes to end the implementation of trade union committees company, seeking a supposed "democratization" in labor relations with the possibility of carrying out collective negotiations whose only limit to this negotiation would present labor rights in the Constitution of the Federal Republic of Brazil 1988 the problem involving the dissertation is presented by the Primer draft bill which lists the said bill as the "modernization" of labor relations, solution to what its authors consider to be a rigid law and beyond. The choice is also studying the bill 4193, 2012 is the hypothesis that the same idea follows the ACE to use collective bargaining as "modernization" of the Consolidation of Labor Laws of 1943 CLT taken by stiff archaic and bureaucratic. In the justification of PL 4193/12 CLT prevents the competitiveness of enterprises and the consequent increases in jobs, and collective bargaining the best option. The dissertation seeks to show that among the discourses surrounding an alleged "modernization" of existing labor legislation in Brazil is possible to realize major elements of the theory and Deregulation Easing Labor, which advocate the fallacious notion that excessive rigidity destroys jobs and prevents dialogue between capital and labor. There came to the premise of these same users be flexible and to dialogue away from the figure of the "Interventor state." In this sense, amid the discursive tessitura found in the texts of the draft and the bill, if part is the hypothesis that through an era of change brought by postmodernity, in a process that installs (economic, social and political ) institutionalization of deregulation and consequent job insecurity verifying, significantly, the lack of concern for social justice, the social value of work and the dignity of the human person. Such neoliberal strategies pose as an obstacle to the development of the country and the CLT itself the principle of worker protection. However, it is noticeable movement towards such contradict the neoliberal arguments to improve and use new principles in Labour Law, the principle of sealing the social regression, in order to protect their achievements stories.